2018
DOI: 10.15666/aeer/1606_75197534
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Technology vs Environmental Regulations in China Based on Dea Malmquist Model and Porter Hypothesis

Abstract: Serious environmental pollution due to the economic boom in China has forced the government to implement environmental regulations. This paper examines the relationship between environmental regulations and technological development in different regions of China. Industry data from 1999 to 2012 using the DEA (Data Envelopment Analysis)-Malmquist productivity index were analyzed. It was found that total productivity growth is mainly caused by the change in technological progress. The environmental regulations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Provincial panel data showed that environmental regulation was positively correlated with industrial green productivity [ 16 ]. Nationally, environmental regulation played a promoting role in technological progress, and so did the eastern region, but there was a restraining effect in the central and western regions [ 35 ]. In addition, micro evidence, such as the analysis of China’s small and medium-sized enterprises, also showed that environmental regulation improved the innovation level [ 36 ].…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Provincial panel data showed that environmental regulation was positively correlated with industrial green productivity [ 16 ]. Nationally, environmental regulation played a promoting role in technological progress, and so did the eastern region, but there was a restraining effect in the central and western regions [ 35 ]. In addition, micro evidence, such as the analysis of China’s small and medium-sized enterprises, also showed that environmental regulation improved the innovation level [ 36 ].…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…One view is that environmental regulation hurts economic development because it incurs additional environmental costs [5]. The other view is that environmental regulation improves economic development because it facilitates innovation [6,7]. However, in China, marine economy is also an important part of the green economy [8], and thus, we know little about the relationship between environmental regulation and the marine economy.…”
Section: Introductionmentioning
confidence: 99%